Nyctalus noctula Schreber 1774 ... - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
15. Common Noctule Nyctalus noctula French: Noctule commune / German: Grof 3er Abendsegler / Spanish: Néctulo mediano Other common names: Noctule, Noctule Bat Taxonomy. Vespertilio noctula Schreber, 1774, France. Nyctalus noctula is sister to the clade including N. lasiopterus and N. aviator. N. plancyi has sometimes been included within this species, but is here recognized as a full species. The name labiatus has been moved to N. plancy: because of the clear morphological differences between N. noctula and labiatus, although labiatus has not been properly compared with N. plancyi; further research is required. Three subspecies recognized. Subspecies and Distribution. N. n. noctula Schreber, 1774 — throughout Europe from Great Britain, France, and Spain E to W Russia, W Kazakhstan, and SW Turkmenistan, including S Scandinavia, Gotland and Oland Is, and Cyprus (Cyprus records somewhat tentatively regarded as this subspecies). Absent throughout much of Iberia and is locally extinct in Portugal. N. n. ... : Published as part of Don E. Wilson & Russell A. Mittermeier, 2019, Vespertilionidae, pp. 716-981 in Handbook of the Mammals of the World – Volume 9 Bats, Barcelona :Lynx Edicions on pages 766-767, DOI: 10.5281/zenodo.6397752 ...